2001
DOI: 10.1051/limn/2001007
|View full text |Cite
|
Sign up to set email alerts
|

Some Rotifera from Ile Amsterdam (Terres Australes et Antarctiques Françaises), with description of Brachionus amsterdamensis sp. nov. (Monogononta : Brachionidae)

Abstract: A preliminary study of the rotifer fauna of He Amsterdam (T.A.A.F.), southern Indian Ocean, yielded seven taxa. Brachionus amsterdamensis sp. nov. is described. Information on the morphology of the trophi of Brachionus dimidiatus is presented. Quelques rotifères de l'Ile Amsterdam (T.A.A.F.), avec description de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Malleate type, with all the characteristics of the genus as described by Segers et al (1993), and found in detailed analyses of other co-generic species (e.g. Ciros-Pé rez et al, 2001;De Smet, 2001). Fulcrum short, flattened laterally (Fig.…”
Section: Descriptionmentioning
confidence: 81%
See 2 more Smart Citations
“…Malleate type, with all the characteristics of the genus as described by Segers et al (1993), and found in detailed analyses of other co-generic species (e.g. Ciros-Pé rez et al, 2001;De Smet, 2001). Fulcrum short, flattened laterally (Fig.…”
Section: Descriptionmentioning
confidence: 81%
“…Trophi of Brachionidae have a species-specific shape and size, and are often used as a reliable taxonomic character (Segers et al, 1993;De Smet, 2001). These structures range in the tens of microns in size, and only Scanning Electron Microscopy (SEM) allows a detailed analysis.…”
Section: Trophi Shape and Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Features like trophi are only found in rotifers; the only species that appears closely related in regard to the complex masticatory apparatus is Gnathostomulid, which also possesses a complex structure with a set of jaws. Nevertheless, only in rotifers, the trophi is used as a tool to identify species as well as an instrument for reconstructing the phylogeny of the organism [3] [4]; furthermore, trophi is the key structure in rotifer taxonomy [5] [6] in genetics with cryptic speciation [7], and morphometric analysis [8].…”
Section: Introductionmentioning
confidence: 99%